2020
DOI: 10.1158/0008-5472.can-19-1427
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contributions of Pre- and Post-EMT Tumor Cells in Breast Cancer Metastasis

Abstract: ◥ Metastases are responsible for the majority of breast cancerassociated deaths. The contribution of epithelial-to-mesenchymal transition (EMT) in the establishment of metastases is still controversial. To obtain in vivo evidence of EMT in metastasis, we established an EMT lineage tracing (Tri-PyMT) model, in which tumor cells undergoing EMT would irreversibly switch their fluorescent marker from RFP þ to GFP þ due to mesenchymal-specific Cre expression. Surprisingly, we found that lung metastases were predomi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 21 publications
3
50
0
Order By: Relevance
“…Third, our current efforts focus on microarray data because the gene signatures utilized by all three methods were identified on this platform. Although the MLR method has been implemented on RNA-seq datasets by regressing the values obtained from microarray and RNA-seq analysis on a case-bycase basis (Kilinc et al, 2019;Lourenco et al, 2020), varying sensitivity of microarray and RNA-seq methods needs to be incorporated for future efforts in assessing these EMT scoring methods systematically.…”
Section: Discussionmentioning
confidence: 99%
“…Third, our current efforts focus on microarray data because the gene signatures utilized by all three methods were identified on this platform. Although the MLR method has been implemented on RNA-seq datasets by regressing the values obtained from microarray and RNA-seq analysis on a case-bycase basis (Kilinc et al, 2019;Lourenco et al, 2020), varying sensitivity of microarray and RNA-seq methods needs to be incorporated for future efforts in assessing these EMT scoring methods systematically.…”
Section: Discussionmentioning
confidence: 99%
“…The number of mesenchymal cells observed in primary cancers in many xenograft studies had been observed to be less than 10%. Although the specific dissemination process of these cells is not yet well documented (Bhatia et al, 2019;Lourenco et al, 2020), enrichment of EMT in circulating tumor cells has supported a role for EMT in the initial steps of metastasis. Various studies have highlighted the role of key EMT TFs, such as Slug and Zeb1, in promoting metastasis of breast and colorectal cancer to liver and lung, respectively (Spaderna et al, 2008;Guo et al, 2012).…”
Section: Role Of Emt In Tumor Initiation Progression and Metastasismentioning
confidence: 99%
“…Orthotopic implantation strategies, such as inoculation into the mammary fat pad, has also improved the recapitulation of the breast cancer in mice (Proia et al, 2011). In conjunction with intravital imaging and fluorophore chemistry, various Cre-Lox lineage tracing approaches have been employed in cell lines, and in injected mouse and zebrafish models, to delineate EMP status of the cells at primary and metastatic sites, and also of encaptured CTCs (Lourenco et al, 2020). These reporter tags are valuable in identification of CTCs and in scenarios of low numbers of cells seeding at secondary niches during metastasis (Zheng et al, 2015;Sikandar et al, 2017).…”
Section: Current Modalities To Investigate Plasticitymentioning
confidence: 99%
“…A correlation has been identified between p53 and the death receptor [29,30], which suggests a significant role of p53 in death receptor-mediated cell death. Metastasis is the main cause of cancer death, and the epithelial-to-mesenchymal transition (EMT) is a crucial process for metastasis [31,32]. Recently, emerging evidence has demonstrated that p53 acts as a negative regulator of EMT via by mediating the expression of EMT markers [33,34] such as Snail, Twist, Slug and Vimentin [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%